2018
DOI: 10.1021/acs.jpca.8b05660
|View full text |Cite
|
Sign up to set email alerts
|

Quenching Effects of Graphene Oxides on the Fluorescence Emission and Reactive Oxygen Species Generation of Chloroaluminum Phthalocyanine

Abstract: The photophysical behavior and reactive oxygen species (ROS) generation by chloroaluminum phthalocyanine (AlClPc) are evaluated by steady state absorption/emission, transient emission, and electron paramagnetic resonance spectroscopies in the presence of graphene oxide (GO), reduced graphene oxide (RGO), and carboxylated nanographene oxide (NGO). AlClPc and graphene oxides form a supramolecular structure stabilized by π-π interactions, which quantitatively quenches fluorescence emission and suppresses ROS gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
(61 reference statements)
0
8
0
1
Order By: Relevance
“…As observed by different groups, including ourselves, GO in its different forms (oxidation level and sheet sizes) is capable of quenching the emission of a myriad of organic dyes . This property has been usually related to GO's π‐conjugated system that makes it a good electron acceptor and also enables it to form nonemissive and very stable supramolecular structures with such conjugated molecules.…”
Section: Resultsmentioning
confidence: 98%
“…As observed by different groups, including ourselves, GO in its different forms (oxidation level and sheet sizes) is capable of quenching the emission of a myriad of organic dyes . This property has been usually related to GO's π‐conjugated system that makes it a good electron acceptor and also enables it to form nonemissive and very stable supramolecular structures with such conjugated molecules.…”
Section: Resultsmentioning
confidence: 98%
“…Recently, Baggio et al further demonstrated the fluorescence quencher profile of one kind of materials obviously quenched fluorescence emission and suppression ROS production. [14] Thus, to develop a novel manganese-based nanomaterial without fluorescence quenching profile could potentially address the need for ICG phototherapy with high efficiency. Although constructing photostable ICG delivery system is crucial for near-infrared light induced ICG phototherapy, the release of the co-delivered autophagy regulation agents in this system is highly needed for synergetic tumor therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Baggio et al. further demonstrated the fluorescence quencher profile of one kind of materials obviously quenched fluorescence emission and suppression ROS production . Thus, to develop a novel manganese‐based nanomaterial without fluorescence quenching profile could potentially address the need for ICG phototherapy with high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Since the graphene materials (GO, various-layer graphene, graphene with different surface functional groups) possess characteristic electronic transitions, electron spectroscopy is a powerful tool for investigating these materials. Graphene is characterized by two peaks in the UV spectrum range: near 230 and 310 nm; these peaks correspond to transitions π−π * and n−π * , respectively [10][11][12][13]. The π−π * absorption band is caused by conjugated bonds in the graphite hexagonal rings, while nonbonding electrons of functional groups of atoms (e. g. oxygen-containing ones) are responsible for the n−π * absorption band.…”
mentioning
confidence: 99%